The Mesozoic magmatic, metamorphic, and tectonic evolution of the eastern Gangdese magmatic arc, southern Tibet - Zhang, Z-M; Ding, H-X; Dong, X; Tian, Z-L; Palin, RM; Santosh, M; Chen, Y-F; Jiang, Y-Y; Qin, S-K; Kang, D-Y; Li, W-T (Geological Society of America, 2021)
Magmatic arcs are natural laboratories for studying the growth of continental crusts. The Gangdese arc, southern Tibet, is an archetypal continental magmatic arc that formed due to Mesozoic subduction of the Neo-Tethyan oceanic lithosphere; however, its formation and evolution remain controversial. In this contribution, we combine newly reported and previously published geochemical and geochronological data for Mesozoic magmatic rocks in the eastern Gangdese arc to reveal its magmatic and metamorphic histories and review its growth, thickening, and fractionation and mineralization processes. Our results show that: (1) the Gangdese arc consists of multiple Mesozoic arc-type magmatic rocks and records voluminous juvenile crustal growth. (2) The Mesozoic magmatic rocks experienced Late Cretaceous granulite-facies metamorphism and partial melting, thus producing hydrous and metallogenic element-rich migmatites that form a major component of the lower arc crust and are a potential source for the Miocene ore-hosting porphyries. (3) The Gangdese arc witnessed crustal thickening and reworking during the Middle to Late Jurassic and Late Cretaceous. (4) Crystallization-fractionation of mantle-derived magmas and partial melting of thickened juvenile lower crust induced intracrustal chemical differentiation during subduction. We suggest that the Gangdese arc underwent the following main tectonic, magmatic, and metamorphic evolution processes: normal subduction and associated mantle-derived magmatism during the Late Triassic to Jurassic; shallow subduction during the Early Cretaceous and an associated magmatic lull; and mid-oceanic ridge subduction, high-temperature metamorphism and an associated magmatic flare-up during the early Late Cretaceous, and flat subduction, high-temperature and high-pressure metamorphism, partial melting, and associated crust-derived magmatism during the late Late Cretaceous. Key issues for further research include the temporal and spatial distributions of Mesozoic magmatic rocks, the evolution of the components and compositions of arc crust over time, and the metallogenic processes that occur in such environments during subduction.